2020
DOI: 10.1002/aenm.202002989
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Self‐Assembled Monolayers for Perovskite Solar Cells Interface Engineering to Address Efficiency and Stability

Abstract: the majority of the market shares as compared to next-generation thin-film PV technologies. Nevertheless, technological challenges in improving efficiencies and decreasing the high-energy requirements connected to the fabrication of silicon PV results in a higher global warming potential. In an effort to achieve lower fabrication cost and higher efficiencies, different types of thin-film PV technologies have been developed including dyesensitized solar cells, [2,3] organic solar cells, [4,5] copper indium tin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
148
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 168 publications
(273 reference statements)
1
148
0
Order By: Relevance
“…[ 24 ] Typically, SAMs usually consist of rod‐like molecules comprising an anchoring group, mediating the bonding to a specific substrate, a tail (functional) group, governing the deposition of the forthcoming layer and altering the energy level offset at the interface, and a spacer group, connecting both groups and building the SAM matrix. [ 25 ] Based on the interaction such as electrostatic, hydrogen bonding, charge transfer, and covalent bonding, the SAMs can be physisorbed or chemisorbed from solution onto various surfaces and form extremely thin layers, by solution‐processed methods such as spin, blade, dip, spray, and slot‐die coating. [ 26 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] Typically, SAMs usually consist of rod‐like molecules comprising an anchoring group, mediating the bonding to a specific substrate, a tail (functional) group, governing the deposition of the forthcoming layer and altering the energy level offset at the interface, and a spacer group, connecting both groups and building the SAM matrix. [ 25 ] Based on the interaction such as electrostatic, hydrogen bonding, charge transfer, and covalent bonding, the SAMs can be physisorbed or chemisorbed from solution onto various surfaces and form extremely thin layers, by solution‐processed methods such as spin, blade, dip, spray, and slot‐die coating. [ 26 ]…”
Section: Introductionmentioning
confidence: 99%
“…[24] Typically, SAMs usually consist of rod-like molecules comprising an anchoring group, mediating the bonding to a specific substrate, a tail (functional) group, governing the deposition of the forthcoming layer and altering the energy level offset at the interface, and a spacer group, connecting both groups and building the SAM matrix. [25] Based on the interaction such as electrostatic, hydrogen DOI: 10.1002/solr.202100663 Self-assembled monolayers (SAMs) have emerged as effective carrier transport layers in perovskite (PVK) solar cells because of their unique ability to manipulate interfacial property, as well as simple processing and scalable fabrication. However, the defects and pinholes derived from their sensitive adsorption process inevitably deteriorate the final device performance.…”
Section: Introductionmentioning
confidence: 99%
“…As the device power conversion efficiency is a composite result of open circuit voltage (V oc ), short circuit current (J sc ) and fill factor (FF), which can all affected by the morphology/crystallinity of perovskite and its contact with other layers and in turn be modulated by SAM modification, minimizing the number of variables involved may lead to better correlation. [39,40] Here in this report, we modified the nickel oxide surface with a series of para-substituted phenylphosphonic acid SAMs as the HTL in the fabrication of PSC to investigate their effect on the device performance. The different substituents (electron-donating CH 3 O-, H-and electronwithdrawing CN-groups) impart different molecular dipoles to the molecules so that when anchored to the NiO x surface, the work function (WF) of the NiO x HTL can be tuned with respect to the valence level of the perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
“…Bush et al [90] reported a power conversion efficiency of 23.6% for a monolithic perovskite/silicon tandem cell that operated successfully for 1000 hours under a damp heat test (85°C and 85% relative humidity). In addition, self-assembled monolayers, which are ordered arrays of organic molecules, have been utilized as interfacial layers in PSCs, in order to improve their efficiency and stability [91].…”
Section: Future Outlook and Challengesmentioning
confidence: 99%